Development of Geographical Information Systems Applications for Local Government Organizations: the Case of the Rhodes Municipality, Greece - Stelios Gialis; Polyzois Kanelleas (European Regional Science Association (ERSA), 2006)
The present recommendation summons up matter from a project in progress, concerning the possibilities and conditions of founding a Social Geographical Information System (GIS) in the Municipality of Rhodes. It is argued that, on the level of local societies and their self-administration, the importance of GIS can prove decisive for the rational management of resources and mainly for a better service of the citizens. Local governments, being that very institution at the closest possible relationship and contact with the resident-citizen, are called to cope with a constantly expanding spectrum of functions and services, often with insufficient infrastructures and limited resources. Today's stage of the applied development of the GIS technology permits an overall arrangement and regulation of a series of functions that are important elements of everyday life in a city. In this sense, the use of GIS, although in the beginning seems as an "unnecessary luxury" for Greek administrational matters, can contribute in a creative way to the realization of the institutional role of local government organizations, to the accomplishment of the declared goals of each municipal authority but also to the saving of time and expenses. However, beyond the applications of GIS related to the improvement of a city's functions, and which are the most frequent, there is a whole constellation of additional uses that are often downgraded or ignored. It is about those dimensions and applications, during which the GIS are utilized as an implement of social studies and search, as a mechanism of tendency diagnosis, as a starting point for awareness on the problems of urban areas and of their residents. It is the perspective and necessity of such applications that we are trying not to downgrade in the present, initial stage of development of a "Social GIS for the Municipality of Rhodes". Our fundamental point of view is that no modern "leading-edge" technology, no advanced implement is by itself a panacea. It can simply assist the development procedures, when it is in the right hands and with the appropriate staff, information and infrastructure. Procedures that have finally reference to the level of central or local political choices but also to the disposition, dynamic or not dynamic, of the body politic for interference and action.
Keywords: 330